The roles of def6a and swap70b in zebrafish embryogenesis and haematopoiesis and DEF6 interactome analysis in Jurkat T cells - Akdeniz, Deniz (2018)
Medio-lateral narrowing (convergence) and anterior-posterior elongation (extension) are two of the most important cell movements of the gastrulation period leading to the formation of embryonic body axis. In vertebrates, convergence and extension (CE) cell movements are regulated by the non-canonical Wnt/Planar cell polarity (PCP) signalling pathway which requires the activation of its downstream effectors, Rho GTPases. DEF6 and SWAP70 are guanine nucleotide exchange factors (GEFs) catalysing the activation of Rho GTPases to regulate the re-arrangement of actin cytoskeleton, cell polarity and cell movements. Although it has been shown that the zebrafish orthologous, Def6a and Swap70b, act downstream of Wnt5b or Wnt11 signalling pathway, respectively, regulating the CE cell movements during gastrulation, little is known about the underlying molecular mechanisms and direct downstream targets of Def6a and Swap70b. To further elucidate the function of def6a and swap70b within the non-canonical Wnt/PCP signalling pathway, Transcription Activator-Like Effector Nucleases (TALENs)-induced mutagenesis was employed to establish knock-out mutant lines lacking either def6a (qmc811), swap70b (qmc809) or both (qmc813). Phenotypic and whole-mount in situ hybridisation analyses have revealed that the anterior movement and the convergence of the lateral mesendodermal and ectodermal cells were severely impaired in def6a and/or swap70b-deficient zebrafish embryos, indicating that def6a and swap70b are required for normal CE cell movements during gastrulation. Ectopic expression of Cdc42 GTPase robustly rescued the CE cell movement defects in both def6aqmc811/qmc811 and swap70bqmc809/qmc809 homozygous mutant lines whereas ectopic expression of RacI robustly rescued CE cell movement defects only in swap70bqmc809/qmc809 homozygous mutant line, suggesting that Def6a and Swap70b acts upstream of Cdc42 and Cdc42/RacI respectively. Elevated expression of wnt5b and wnt11 detected in the mutant lines indicated that abrogation of def6a and swap70b functions interfered with Cdc42/RacI-mediated Jnk activation that negatively regulates expression of wnt11 and perhaps wnt5b. In adult def6a and/or swap70b-deficient fish, a decreased number of myeloid population was observed, suggesting that both proteins are required for balanced cell differentiation during haematopoiesis. Generation of the double homozygous mutant line revealed that def6a and swap70b act in a partially redundant manner during zebrafish embryogenesis and in a non-redundant manner during haematopoiesis. DEF6 is highly expressed in T cells and plays an immunoregulatory role in cell polarity-induced immunological synapse (IS) formation, T cell receptor (TCR) signalling, T cell activation, differentiation and inflammatory responses. Recently, it has been shown that DEF6 may also be involved in the mRNA surveillance and translation. However, the molecular mechanisms that it may be involved in and its interactors in T cells are still unknown. Hence, a novel method, BioID, which enables the promiscuous biotinylation of proximal and interacting proteins of a target protein in mammalian cells, was adapted to identify DEF6 interactome in Jurkat T cells. Notably, in vivo BioID-DEF6 fusions yielded 127 clusters of interacting and vicinal proteins, including 2 known binding partners, Rac2 and PKC and 1 known close proximity partner, PABP. GO-term classification of the identified proteins showed that the proteins are enriched not only in actin cytoskeleton organisation and mRNA translation, but also in transcription, mRNA splicing/processing, protein folding/modification and metabolic processes. Co-localisation of DEF6 with Coronin1A (CORO1A), an actin cytoskeleton regulator during IS formation, in resting and activated cells provided proof of principle for the interactome analysis suggesting that DEF6 is a multifunctional protein involved in the regulation of cytoskeletal organisation, transcription, mRNA splicing, protein folding/processing and metabolic processes.